2017
DOI: 10.5014/ajot.2018.029413
|View full text |Cite
|
Sign up to set email alerts
|

Specific Sensory Techniques and Sensory Environmental Modifications for Children and Youth With Sensory Integration Difficulties: A Systematic Review

Abstract: This systematic review examined the effectiveness of specific sensory techniques and sensory environmental modifications to improve participation of children with sensory integration (SI) difficulties. Abstracts of 11,436 articles published between January 2007 and May 2015 were examined. Studies were included if designs reflected high levels of evidence, participants demonstrated SI difficulties, and outcome measures addressed function or participation. Eight studies met inclusion criteria. Seven studies eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 33 publications
0
36
1
2
Order By: Relevance
“…Our findings on improved behavior under SADE are consistent with the previous studies presented by Shapiro et al and Cermak et al . A recent systematic review of specific sensory techniques and sensory environmental modifications for children with sensory integration difficulties concluded that there is moderate evidence supporting the use of SADE …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings on improved behavior under SADE are consistent with the previous studies presented by Shapiro et al and Cermak et al . A recent systematic review of specific sensory techniques and sensory environmental modifications for children with sensory integration difficulties concluded that there is moderate evidence supporting the use of SADE …”
Section: Discussionmentioning
confidence: 99%
“…Our findings on improved behavior under SADE are consistent with the previous studies presented by Shapiro et al and Cermak et al [22][23][24] A recent systematic review of specific sensory techniques and sensory environmental modifications for children with sensory integration difficulties concluded that there is moderate evidence supporting the use of SADE. 29 The difference in the physiological outcomes of the children with DD undergoing SADE or RDE was inconclusive. The participants' heart rate and oxygen saturation were recorded in the beginning and at the end of each visit to collect objective data reflecting on their physiological distress during a dental appointment.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, automatic and deliberate processes from dual-tiered models inform effective treatment planning by supporting the alignment of treatment approaches across distributed systems. Integrating awareness of arousal regulation with sensorimotor-based treatments are necessary, including a promising trend towards decreasing EDA magnitude (e.g., Miller et al, 2007;Bodison and Parham, 2018;Foitzik and Brown, 2018). Sensorimotor-focused treatment strategies can impact a variety of distributed properties and benefit from being coupled with socio-emotional and play-based relational approaches (Greenspan et al, 1998;Bundy et al, 2008;Lillas et al, 2018;Pfeiffer et al, 2018;Roberts et al, 2018;Schaaf et al, 2018;Delahooke, 2019;Porges et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…The environmental modifications applied in this study were teaching changes in household structure and providing and using applicable sensory tools. The most common method to modify the environment was video media restrictions, reducing unnecessary visual and auditory stimuli, providing individual space, and vestibular and proprioceptive stimuli [23].…”
Section: Home Environmental Modificationmentioning
confidence: 99%